The study of financial performance of Kolej Poly-Tech Mara Batu Pahat Sendirian Berhad for the year 2005 to 2010 / Siti Farhana Kasri - Kasri, Siti Farhana (2011)
This research is focus on the analysis of financial ratio in order to see the financial performance of company. The data is collected from both of the primary and secondary sources. This study is focus on the annual audited report of Kolej Poly-Tech Mara Batu Pahat from the year 2005 until 2010. Other sources from primary data such as direct observation and interview also method that already used. From the analysis of financial ratio, researcher can see that company already manage their financial site well except for some year like 2009. On the 2009, the quick ratio shows a bad result because of economic downturn on that year. In this research, by analyzing the financial ratio, researcher can determine the credit analysis, capital structure and solvency, return on investment, operating performance, and asset utilization. Because of all the reason, the researcher conducts the analysis of ratio to identify the financial performance of company. Other than that, researcher can determine the strength and weaknesses in order to make an improvement to meet an organization’s goals.